Plasma Cell Leukaemia - DR.DAPHNE FONSECA; DR.FAIQ AHMED; DR.SUDHA MURTHY; DR.SENTHIL RAJAPPA (International Journal of Pharma and Bio Sciences, 2012)
Primary plasma cell leukemia (PCL) is a rare plasma cell disorder, and current knowledge regarding survival in this disease is limited to small series of patients. Although there has been significant improvement in the survival of patients with multiple myeloma (MM) over the past few decades, it is not known whether there has been a similar trend for PCL. The incidence of adverse prognostic factors is significantly higher in PCL versus MM. Although similar,PCL exhibits distinct clinical,immunophenotypic and cytogenetic features that distinguish it from MM.We report three cases of Plasma cell leukaemia of which one was a primary plasma cell leukaemia and the other two cases were secondary plasma cell leukaemias.